Evaluation of marginal leakage of amalgam restorations: mercury versus gallium (Pesquisa Odontológica Brasileira, 2000)
Nowadays, there is an increasing concern about the presence of mercury in amalgam restorations, and alternative alloys were developed as substitutes for this material. In this study, the marginal leakage of two amalgam alloys (with mercury and with gallium) with two adhesive systems (PAAMA and Scotchbond Multipurpose Plus) were evaluated in class V cavities (margins in enamel and cement). Sound human teeth were restored and submitted to 500 cicles (5ºC-55ºC, 15 s in each wash) before immersion in dye ( methylene blue). The teeth were cut and evaluated. The scores were compiled and submitted to statistical analysis (Kruskal-Wallis test with 99% of confidence level). Based on the results, we can conclude that there was a significant difference between the utilized adhesives, and that the best performance was obtained by the Scotchbond Multipurpose Plus system. There was no statistical difference between the amalgam alloys nor between the tooth walls.